Peningkatan Kompetensi Guru Madrasah Dalam Pengembangan Bahan Ajar Berbasis ICT di Madrasah Tsnawiyah Sabilal Al Muhtadin - M. Khalilullah; Subhan; Rian Vebrianto (Tasnim Journal for Community Service, 2020)
A teacher is a key component in the educational system. The technology is developing every time. If a teacher does not keep up with the current development, the teacher will be left behind and the learning process will certainly be abstract. Therefore, the community service team conducts a workshop in improving the teacher’s competence in Islamic school especially in developing the ICT-based teaching material. A media or the teaching material also becomes an important component in facilitating the success of the significant and effective teaching and learning process for students. This community service was conducted in a private Islamic school that was Madrasah Tsanawiyah Sabilal Al Muhtadin. It was done by assisting them in the form of a workshop. From the workshop that has been conducted, the result of an evaluation by the participants showed that the participants were very satisfied with the community service program and they wished that many similar programs will be conducted in a hands-on way. In the implementation, the participants were also satisfied with the knowledge and the skills owned by the lecturer as the executor of the community service program. The government and the stakeholders are expected to be able to connect and cooperate with the lecturers in achieving good cooperation between school, university, and department of education. Thereby, such programs will not be wasted and the participant can get the benefits.